2019
DOI: 10.1016/j.jmii.2018.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Associations between environmental heavy metal exposure and childhood asthma: A population-based study

Abstract: Higher concentrations of blood lead are associated with higher odds of asthma in children aged 2-15 years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(40 citation statements)
references
References 39 publications
2
38
0
Order By: Relevance
“…Inhaled PM induces oxidative stress leading to inflammatory responses in the airways and bronchial hyperreactivity and metal fumes are well-recognised causes of occupational asthma, but the contribution of metal dusts to nonoccupational asthma is less obvious. High blood Pb is correlated with having asthma in children, but the meaning is unclear [107]. Other diseases linked to metal exposures (with or without air pollution) include chronic neurological disorders such as Parkinsonism and Alzheimer's disease (including Al, Cu, Mn,) [11•], renal and liver disorders ( Table 2).…”
Section: Health Outcomes and Responsementioning
confidence: 99%
“…Inhaled PM induces oxidative stress leading to inflammatory responses in the airways and bronchial hyperreactivity and metal fumes are well-recognised causes of occupational asthma, but the contribution of metal dusts to nonoccupational asthma is less obvious. High blood Pb is correlated with having asthma in children, but the meaning is unclear [107]. Other diseases linked to metal exposures (with or without air pollution) include chronic neurological disorders such as Parkinsonism and Alzheimer's disease (including Al, Cu, Mn,) [11•], renal and liver disorders ( Table 2).…”
Section: Health Outcomes and Responsementioning
confidence: 99%
“…Heavy metals that enter the human body through chronic exposure are very difficult to metabolize or decompose, so they accumulate in all tissues and organs over the years and exert chronic damage to the body when they reach a certain threshold (Raehsler et al, 2018). Epidemiological investigations have shown that heavy metals can be detected in the blood, urine, hair, and nails of healthy and diseased people and that the content is correlated with severity of respiration diseases (Wu et al, 2018), cardiovascular diseases (Lamas et al, 2016), neurodegeneration (Bjorklund et al, 2018a;Ghazala et al, 2018;Iqbal et al, 2018) diseases, autism spectrum disorder (Bjorklund et al, 2018b), and obesity (Park et al, 2017;Shao et al, 2017;Wang et al, 2018). Great efforts have been made to reduce heavy metal pollution, but these efforts often have very limited effects (Bisanz et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…A previous study that used age-stratified analysis showed that a higher concentration of lead in the blood was associated with a higher risk of asthma in younger individuals whilst active [35].…”
Section: Discussionmentioning
confidence: 95%